Pseudophlepsius binotatus (Signoret, 1880) sensu lato (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini) is a complex of biological species - Tishechkin, Dmitri Yu. (Zootaxa, 2025)
A study of the male vibrational calling signals, host plants, and morphological characters of Pseudophlepsius binotatus sensu lato showed that in Russia and adjacent countries this taxon includes three biological species. P. binotatus is distributed in the semi-deserts and deserts of the Lower Volga region and Central Asia and feeds on camel thorn (Alhagi spp.). P. abdykulovi sp. nov. described from southeastern Kazakhstan and Kyrgyzstan was collected from Glycyrrhiza spp., Caragana sp., and Halimodendron halodendron. P. septentrionalis stat. nov. inhabits the mixed-grass steppes of southern Russia and Kazakhstan and penetrates into the low mountains and forest zone; it was found on Hamaecytisus ruthenicus and Calophaca soongorica. P. binotatus and P. abdykulovi sp. nov. are indistinguishable by the shape of the male genitalia and differ from each other only by the shape of the teeth on the 2nd valvulae of the ovipositor. P. septentrionalis stat. nov. differs from the other two species by the shape of aedeagus and subgenital plates.